Decreased capillary density in renal cell carcinoma: Evidence from a case report with micro-computerized tomography. Issue 36 (September 2019) - Lin, Tzu-Chun; Chen, Huey-Yi; Yang, You-Rong; Liu, Po-Len; Chen, Yung-Hsiang; Chen, Wen-Chi
Abstract: Rationale: Conventional computerized tomography (CT) examination can differentiate renal cortical tumor from urothelial carcinoma on the basis of the highly contrast-enhanced vessels in renal cortical tumors. However, the capillary distribution of renal cell carcinoma (RCC) has been under-investigated. Here, we present a micro-CT image of tumor tissue in a patient with RCC. Patient concerns: The patient was a 72-year-old woman with a past history of diabetes mellitus and hypertension. She did not have tumor-related symptoms. Diagnosis and interventions: The tumor was diagnosed using abdominal CT during her yearly routine health check. After radical nephrectomy, the tumor was subjected to pathological examination and micro-CT imaging. Pathological analysis confirmed a clear cell renal carcinoma. The capillary distribution of the tumor was significantly lesser than that of the normal cortex on micro-CT image. Lessons: Microvessels of RCC can be detected by micro-CT. We also found that the distribution of microvessels was uneven and lower than that in the normal cortex in this case. For a more general diagnosis, more micro-CT images of RCC tumors are needed. Abstract : Supplemental Digital Content is available in the text